An unusual presentation of ovarian dermoid cyst: a case report and review of literature - Azami, Mohamed Amine (Obstet Gynecol Sci, 2018)
Dermoid cysts or mature cystic teratoma are the most common type of ovarian germ cell tumor. It may be complicated by torsion, rupture, chemical peritonitis and malignant change but is rarely complicated by infection. We present a case of an ovarian dermoid cyst with super-infection caused by Schistosoma haematobium (S. haematobium). We present here a case of incidental finding of S. haematobium eggs in an infected cystic teratoma of the ovary because of the rare occurrence of this lesion. A 45-year-old Moroccan woman admitted to the gynecological department because of abdominal pain and fever. Gynecological examination, ultrasonography, and abdominopelvic computed tomography scan revealed an ovarian mass thought to be a dermoid cyst. The pathological evaluation suggested infected ovarian dermoid cyst with the presence of adult worm in the tumor, contains same eggs of S. haematobium. Super-infection of an ovarian dermoid cyst is a rare event, and the association with S. haematobium is extremely rare in the literature.